C♯ 4.0 unleashed - De Smet, Bart (Sams, 2011)
C# 4.0 Unleashed is a practical reference focusing on the C# language and the .NET platform as a whole. While covering the language in lots of detail, it also provides enough coverage of various popular .NET technologies and techniques (such as debugging) for the reader to be successful on the .NET platform. The in-depth coverage of the language features is crucial to the success of a developer. Knowing exactly where and why to use certain language features can boost efficiency significantly. This book differs from other works by going into enough depth on how things work, while not being a clone of the formal language specification. Concise anecdotes with concrete samples illustrate how certain language features behave, and also point out possible caveats in using them. On the side of platform coverage, the author provides a gentle introduction to the wide landscape of the .NET platform, following a logical structure that reflects the high-level architecture of an application: presentation, logic, data, connectivity, et cetera In the .NET part of the book there's coverage of relevant new technologies such as cloud computing, modeling, and parallel programming - things that will gain much more attention moving forward. Provides valuable insight into the C# language and the .NET Framework - not just "what" but also the "how" and "why" of the language and framework features Covers using C# with new major technologies, such as cloud computing, SharePoint, and ASP.NET MVC Author is Microsoft insider Will be day and date with the release of C# 4.0.